Pharmacologic Inhibition of the NLRP3 Inflammasome Preserves Cardiac Function After Ischemic and Nonischemic Injury in the Mouse. Issue 1 (July 2015) - Marchetti, Carlo; Toldo, Stefano; Chojnacki, Jeremy; Mezzaroma, Eleonora; Liu, Kai; Salloum, Fadi N.; Nordio, Andrea; Carbone, Salvatore; Mauro, Adolfo Gabriele; Das, Anindita; Zalavadia, Ankit A.; Halquist, Matthew S.; et al.
Abstract : Background: Sterile inflammation resulting from myocardial injury activates the NLRP3 inflammasome and amplifies the inflammatory response mediating further damage. Methods: We used 2 experimental models of ischemic injury (acute myocardial infarction [AMI] with and without reperfusion) and a model of nonischemic injury due to doxorubicin 10 mg/kg to determine whether the NLRP3 inflammasome preserved cardiac function after injury. Results: Treatment with the NLRP3 inflammasome inhibitor in the reperfused AMI model caused a significant reduction in infarct size measured at pathology or as serum cardiac troponin I level (−56% and −82%, respectively, both P < 0.001) and preserved left ventricular fractional shortening (LVFS, 31 ± 2 vs. vehicle 26% ± 1%, P = 0.003). In the non-reperfused AMI model, treatment with the NLRP3 inhibitor significantly limited LV systolic dysfunction at 7 days (LVFS of 20 ± 2 vs. 14% ± 1%, P = 0.002), without a significant effect on infarct size. In the doxorubicin model, a significant increase in myocardial interstitial fibrosis and a decline in systolic function were seen in vehicle-treated mice, whereas treatment with the NLRP3 inhibitor significantly reduced fibrosis (−80%, P = 0.001) and preserved systolic function (LVFS 35 ± 2 vs. vehicle 27% ± 2%, P = 0.017). Conclusions: Pharmacological inhibition of the NLRP3 inflammasome limits cell death and LV systolic dysfunction after ischemic and nonischemic injury in the mouse. Abstract : Supplemental Digital Content is Available in the Text.